Historiography Research of Organizational and Pedagogical Foundations of the Childrenʼs Home Activity in Ukrainian Educational System (1920-s – Mid of 1930-s) - Liliya Korobova (Pedagogical Discourse, 2013)
The historiography research peculiarities of organizational and pedagogical foundations of the childrenʼs home activity in Ukrainian educational system in 1920-s – mid 1930-s are studied. In particular the author proposes the periodization of historiographical analysis taking into consideration the formation and development of native history of pedagogics periodization. It includes the following perods: 1) the first period of historiography of socializing functions of children’s home in the Ukrainian educational system (1920-1930-s) 2) the second period (1940-1990-s), the third period of the research of historiography begins since 1990 and continues since that time. The author, in particular, profoundly analyzed all mentioned periods and made proper conclusions.